EXPLORING THE RELATIONSHIP BETWEEN SELF-ESTEEM AND PUBLIC SPEAKING ANXIETY AMONG NIGERIAN POSTGRADUATE STUDENTS - Kamaldeen Tinuke Rahmat; M. O Osere (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Public speaking anxiety (PSA) is one of the most common psychological barriers faced by Postgraduate students in Nigeria. Public communication skills are quite urgent in the academic and professional world. However, students still experience anxiety when conveying ideas or research results in open forums. The results of the study showed that self-esteem affects the level of anxiety. This study examines the relationship between self-esteem and public speaking anxiety among Postgraduate students at Al-Hikmah University, Ilorin. This study used a descriptive correlational survey design with a sample size of 96 students. Data were analyzed using the Pearson Product-Moment correlation technique. The results showed that 56.3% of respondents experienced low levels of anxiety, 29.2% moderate, and 14.6% high. Meanwhile, the results of the correlation analysis showed a weak negative relationship between self-esteem and public speaking anxiety (r = -0.109; p = 0.290). Based on these findings, it can be concluded that self-esteem is not the primary predictor of public speaking anxiety. Therefore, broader interventions such as public speaking training and counseling services are needed to help students with high levels of anxiety.